`sqrt(-36)` Topic: Math 1 Answer | Add Yours pramodpandey | College Teacher | (Level 3) Valedictorian Posted on April 23, 2013 at 7:28 AM (Answer #1) Since we know `36=6xx6` `=6^2` `i^2=-1` Therefore `sqrt(-36)=sqrt(36i^2)` `=sqrt(6^2i^2)` `=sqrt((6i)^2)` `=6i` We’ve answered 397,388 questions. We can answer yours, too. Ask a question

pramodpandey | College Teacher | (Level 3) Valedictorian Posted on April 23, 2013 at 7:28 AM (Answer #1) Since we know `36=6xx6` `=6^2` `i^2=-1` Therefore `sqrt(-36)=sqrt(36i^2)` `=sqrt(6^2i^2)` `=sqrt((6i)^2)` `=6i`